Georgia : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2001)
The Georgian financial system is small by international standards and by comparison with countries in the region. The vulnerabilities and policy challenges in the Georgian financial system are closely linked to the transitional stage of the economy. The legal framework governing the financial sector needs improvement. The assessment of compliance with the Basel Core Principles (BCP) for Effective Banking Supervision (EBS) found that while substantial advances in bank supervision have occurred during the past two to three years, there are several areas in need of improvement.